TECHNO-ECONOMY STUDY OF MERCURY REMOVAL TECHNOLOGY FROM CRUDE OIL USING NON-ASSOCIATED STRIPPING GAS - Wira Utama, Satya
Mercury is a hazardous impurity found in crude oil. During the oil drilling process, mercury can partition into the produced oil, gas, and water. Mercury poses risks to human health as it can damage the lungs and disrupt the central nervous system. Additionally, mercury can corrode aluminum by forming an amalgam. These hazards necessitate the removal of mercury from crude oil to reach safe limits before further processing. Mercury removal can be achieved through methods such as precipitation, adsorption, or thermal methods. However, these methods face challenges due to the high content of solid particles in crude oil, which reduces mercury removal efficiency. Thermal conversionbased mercury removal processes using non-associated gas jets have proven to be highly efficient and economically viable. In this study, a mercury removal method from crude oil was designed using thermal conversion with non-associated gas jets. The research involved validating fluid data packages using mercury solubility data in water and experimental data on the distribution of metallic mercury in oil-water equilibrium. Experiments were conducted using synthetic oil mixed with water at 10-40% water cut. The oil and water were separated, and the concentration of mercury was analyzed for each component. The validated data packages were then used to design simulations using Aspen HYSYS software, comparing two variations of the Gas to Oil ratio at 15 and 20 scf/bbl. Based on literature data, it is known that the reduction reaction of ionic mercury to metallic mercury follows a first-order reaction kinetics with a rate constant (k0) value of 8.32 × 1011 and an activation energy (Ea/R) value of 13,305 K. Simulation results show that Gas-to-Oil Ratio (GOR) and temperature are directly proportional to mercury removal efficiency. In order to achieve the same efficiency between GOR 15 and GOR 20, the operating temperature of the reactor is increased in GOR 15 to obtain additional stripping gas. The increase in temperature in the reactor is balanced by a decrease in volume to achieve the same thermal conversion. The optimal conditions for mercury removal are a heating temperature of 206.2°C for GOR 15 scf/bbl and 196.1°C for GOR 20 scf/bbl. The cost of mercury removal processing is 1.40 USD for GOR 15 scf/bbl and 1.35 USD for GOR 20 scf/bbl.